2022
DOI: 10.2196/34753
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Decision Support System for Assessing the Risk of Cervical Cancer: Development and Evaluation Study

Abstract: Background Cervical cancer has been recognized as a preventable type of cancer. As the assessment of all the risk factors of a disease is challenging for physicians, information technology and risk assessment models have been used to estimate the degree of risk. Objective The aim of this study was to develop a clinical decision support system to assess the risk of cervical cancer. Methods This study was cond… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…[26] used an arti cial neural network to construct a clinical decision support system for predicting quality of life among elderly people, and the results showed that the clinical decision support system, which was designed based on the CFBP, is an effective tool for improving the quality of life of elderly people. Nasrin Chekin et al [27] constructed a clinical decision support system for assessing the risk of cervical cancer, and the study con rmed that the system can facilitate the process of identifying people who are at risk of developing cervical cancer. In addition, the system can help to increase the quality of health care and reduce the costs associated with the treatment of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[26] used an arti cial neural network to construct a clinical decision support system for predicting quality of life among elderly people, and the results showed that the clinical decision support system, which was designed based on the CFBP, is an effective tool for improving the quality of life of elderly people. Nasrin Chekin et al [27] constructed a clinical decision support system for assessing the risk of cervical cancer, and the study con rmed that the system can facilitate the process of identifying people who are at risk of developing cervical cancer. In addition, the system can help to increase the quality of health care and reduce the costs associated with the treatment of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%